Critical factors in community informatics : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Production Engineering at Massey University, Palmerston North, New Zealand - Mason, David Douglas Miller (Massey University, 2003)
Community Informatics is a new field of research that studies how information and communications technologies can be used to improve the quality of life of communities. The use and acceptance of technology is unpredictable. Early Community Informatics research found that deploying information technology with the aim of improving communities was seldom successful. Research has been done to identify the factors that might have a bearing on the outcome, but no definitive answer has emerged, and little work has been done on evaluating the effect of the methodology on the outcome. This research set out to establish what the critical factors were, and to determine whether a specific community informatics methodology could be designed. The objective of this research was to design a Community Informatics methodology, a way of introducing ICT into communities, that would ensure a successful economic outcome. The strategy was to use tourism as the catalyst for economic growth. The outcome sought was a self sustaining, locally owned and scalable tourism product which would provide jobs initially and in the longer term would bring money into the local economy and lead to a revitalisation of the community. The research was in two parts. The first part consisted of prototyping ecommerce Internet sites of increasing scope and complexity using a participative methodology within the socio-economic computer systems design paradigm. The work involved four organisations: the Katherine Mansfield Birthplace, the Spa Association of New Zealand and two large hotels. The outcome was a generic ecommerce model and a participative methodology for implementing that model. The second part of the research involved applying the prototype methodology to communities in isolated parts of New Zealand. The communities involved were located in North Hokianga, Mahia and East Cape. The final outcome was a community owned and maintained ecommerce Internet site that could form the basis for a tourism led economy. This research has shown that by using the right methodology it is possible to create a viable community based ecommerce application, and that there are four critical factors in Community Informatics: leadership, motivation, consensus and the methodology used.
Keywords: System design; Community organisation; Computer network resources; Tourism; Electronic commerce; New Zealand; Fields of Research::350000 Commerce, Management, Tourism and Services::350500 Tourism